2014
DOI: 10.1186/1750-1326-9-59
|View full text |Cite
|
Sign up to set email alerts
|

Structural biology of presenilin 1 complexes

Abstract: The presenilin genes were first identified as the site of missense mutations causing early onset autosomal dominant familial Alzheimer's disease. Subsequent work has shown that the presenilin proteins are the catalytic subunits of a hetero-tetrameric complex containing APH1, nicastrin and PEN-2. This complex (variously termed presenilin complex or gamma-secretase complex) performs an unusual type of proteolysis in which the transmembrane domains of Type I proteins are cleaved within the hydrophobic compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…Pen-2 is required for maturation of Presenilin; Aph-1a (or Aph-1b) is required for proper assembly of the γ-secretase complex. Finally, Nicastrin, which is not needed for catalytic activity or substrate recognition (Zhao et al, 2010) is involved in complex stabilization and perhaps substrate selection (Li et al, 2014a). The CryoEM data showed that the 20 TM helices adopt a horseshoe-like structure with a Presenilin and a Aph-1 molecule located in the center and the extracellular domain of Nicastrin forming a head domain that sits atop the hollow region of the horseshoe (Figure 1).…”
Section: ) Proteolytic Cleavage and Charge Distribution At/below Thementioning
confidence: 99%
See 1 more Smart Citation
“…Pen-2 is required for maturation of Presenilin; Aph-1a (or Aph-1b) is required for proper assembly of the γ-secretase complex. Finally, Nicastrin, which is not needed for catalytic activity or substrate recognition (Zhao et al, 2010) is involved in complex stabilization and perhaps substrate selection (Li et al, 2014a). The CryoEM data showed that the 20 TM helices adopt a horseshoe-like structure with a Presenilin and a Aph-1 molecule located in the center and the extracellular domain of Nicastrin forming a head domain that sits atop the hollow region of the horseshoe (Figure 1).…”
Section: ) Proteolytic Cleavage and Charge Distribution At/below Thementioning
confidence: 99%
“…Perhaps the best studied of these parameters has been the Su(H)-paired-sites (SPS, or Su(H)-paired-sites) that were originally described in the Enhancer of split (E(spl) complex in Drosophila and have been found in CRMs of genes from insects to mammals (Bailey and Posakony, 1995; Hass et al, 2015; Liu and Posakony, 2012, 2014; Nellesen et al, 1999). SPS sites consist of two CSL sites that are found in a specific orientation (head-to-head) and spacing (~15 to 17 nucleotides apart).…”
Section: ) Free At Last: the Latest Insights On Nicd Function In Thementioning
confidence: 99%
“…We focused our analysis here on a prototypical pathological process, familial AD (FAD) due to mutations in presenilin (PSEN)-1 or -2 genes, as the underlying genetic cause is partly established and molecular assays for PSEN-associated activities are well described (Levy-Lahad et al, 1995b; Levy-Lahad et al, 1995a; Rogaev et al, 1995; Sherrington et al, 1995; Li et al, 2014; De Strooper and Chavez Gutierrez, 2015). PSENs are essential components of the γ-secretase (GS) complex, which is a heteromultimeric complex required for intramembranous cleavage of substrates such as the βCTF/C99 fragment of amyloid precursor protein (APP) (De Strooper et al, 2012; Andrew et al, 2016; Selkoe and Hardy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a typical proteinopathy, AD is characterized by abnormal proteins with mutations or post-translational modifications that interfere with their normal functions and status (soluble or not) and metabolism inside the cell [15][16][17]. Mutant proteins are the amyloid precursor protein (APP) and presinilins 1 and 2 (PS1 and PS2).…”
Section: Introductionmentioning
confidence: 99%